MiRTarBase update 2018: a resource for experimentally validated microRNA-target interactions. Issue Volume 46:Issue D1(2018) (6th November 2017) - Chou, Chih-Hung; Shrestha, Sirjana; Yang, Chi-Dung; Chang, Nai-Wen; Lin, Yu-Ling; Liao, Kuang-Wen; Huang, Wei-Chi; Sun, Ting-Hsuan; Tu, Siang-Jyun; Lee, Wei-Hsiang; Chiew, Men-Yee; Tai, Chun-San; et al.
Abstract: MicroRNAs (miRNAs) are small non-coding RNAs of ∼ 22 nucleotides that are involved in negative regulation of mRNA at the post-transcriptional level. Previously, we developed miRTarBase which provides information about experimentally validated miRNA-target interactions (MTIs). Here, we describe an updated database containing 422 517 curated MTIs from 4076 miRNAs and 23 054 target genes collected from over 8500 articles. The number of MTIs curated by strong evidence has increased ∼1.4-fold since the last update in 2016. In this updated version, target sites validated by reporter assay that are available in the literature can be downloaded. The target site sequence can extract new features for analysis via a machine learning approach which can help to evaluate the performance of miRNA-target prediction tools. Furthermore, different ways of browsing enhance user browsing specific MTIs. With these improvements, miRTarBase serves as more comprehensively annotated, experimentally validated miRNA-target interactions databases in the field of miRNA related research. miRTarBase is available at http://miRTarBase.mbc.nctu.edu.tw/ .